"There's nothing that compares to it": A grounded theoretical analysis of the experiences of police hostage and crisis negotiators. Issue 3 (10th June 2019) - Grubb, Amy Rose; Brown, Sarah J.; Hall, Peter; Bowen, Erica
Abstract : Purpose: Hostage and crisis negotiators serve a vital function within society by resolving hostage/crisis incidents. This role, performed by specially trained police "volunteers", helps to prevent numerous fatalities and forms an important part of the modern policing repertoire. There is limited research that identifies the experiences of police officers that dedicate their lives to saving others by volunteering in this capacity. This paper aims to provide an insight into this fundamental police role using negotiator's personal narratives. Design/methodology/approach: This study consisted of an exploratory qualitative grounded theoretical analysis of semi-structured interviews conducted with 15 negotiators from nine English police forces. Findings: The analysis revealed 3 primary, 7 secondary and 23 tertiary categories that form a conceptual model of the negotiator experience. The three primary categories consisted of "negotiator positives", "negotiator negatives" and "negotiator ambivalences", which provide an insight into the experiences and identities of negotiators in England. Practical implications: The findings identify several positive factors that could be used to market the role more effectively within police forces and enhance future recruitment processes. Equally, the findings highlight several operational and organisational issues that have a negative impact on the negotiator experience. The findings are, therefore, discussed in light of the practical implications for negotiator training/continuing professional development, policy and practice. Originality/value: This paper depicts the findings from one of the first qualitative analyses of negotiator experiences and provides a unique insight into the negotiator role from an Anglo-centric perspective.